2009
DOI: 10.1007/s00595-008-3909-1
|View full text |Cite
|
Sign up to set email alerts
|

Gefitinib and a ventriculo-peritoneal shunt to manage carcinomatous meningitis from non-small-cell lung cancer: Report of two cases

Abstract: The prognosis of patients with carcinomatous meningitis from non-small-cell lung cancer (NSCLC) remains poor, and the available treatment options for the lung cancer do not relieve the severe symptoms of this sequela. We report the successful treatment of two cases of carcinomatous meningitis caused by NSCLC, using gefitinib and a ventriculo-peritoneal (V-P) shunt. The first patient was a 43-year-old woman with pT1N0M0 adenocarcinoma. Multiple brain and vertebral metastases were found 13 months after surgery. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 20 publications
1
2
0
Order By: Relevance
“…In our study, 23 of 30 developed LM during treatment with EGFR-TKI. After the diagnosis of LM, the 36 patients who received EGFR-TKIs achieved significantly longer iPFS LM and OS LM than patients who did not (median iPFS LM 3.9 vs. 2.7 months, p = 0.019; median OS LM 10 vs. 3.3 months, p = 0.002), and these findings are consistent with those from previous studies [5, 6, 22, 23]. Li et al [5] showed that patients who received EGFR-TKIs after LM diagnosis had significantly longer survival compared with those who did not (10.0 vs. 3.3 months; p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…In our study, 23 of 30 developed LM during treatment with EGFR-TKI. After the diagnosis of LM, the 36 patients who received EGFR-TKIs achieved significantly longer iPFS LM and OS LM than patients who did not (median iPFS LM 3.9 vs. 2.7 months, p = 0.019; median OS LM 10 vs. 3.3 months, p = 0.002), and these findings are consistent with those from previous studies [5, 6, 22, 23]. Li et al [5] showed that patients who received EGFR-TKIs after LM diagnosis had significantly longer survival compared with those who did not (10.0 vs. 3.3 months; p < 0.001).…”
Section: Discussionsupporting
confidence: 90%
“…11 Some authors have reported that EGFR TKIs were effective in treating LC in patients with EGFR mutations. [12][13][14] In several retrospective studies, EGFR TKI therapy for LC was found to prolong survival, but the impact of EGFR mutations was not clear because of the small number of patients who underwent EGFR gene testing. [15][16][17][18][19][20] Gefitinib and erlotinib were available commercially in Taiwan in 2003 and 2006, respectively, to treat metastatic lung cancer.…”
mentioning
confidence: 99%
“…These findings might provide valuable information for the management of gefitinib-responders. Although the survival benefit is controversial, gefitinib may also be useful for the treatment of carcinomatous meningitis from NSCLC to improve neurological dysfunction (41,42,43 …”
Section: Gefitinib (Table 2)mentioning
confidence: 99%